Linear Water Erosion Incisions in the Central-West Region of Brazil: A Bibliometric Analysis - Kássio Samay Ribeiro Tavares; Selma Simões de Castro (Revista Brasileira de Geomorfologia)
This study presents the results of a comprehensive bibliometric analysis of research on linear water erosion incisions in the Central-West region of Brazil. A total of 91 documents, including scientific articles, dissertations and academic theses, were analyzed to map the research trends and patterns in this field. The results indicate a predominance of geospatial and geodynamic studies. A multidisciplinary methodological approach is evident in 71% of the studies that combine multiple procedures to obtain more robust results. Most studies are multifactorial, using indicators of vegetation, land use and management, and geomorphology, reflecting the complexity of the processes involved. The main research focuses include modeling, mapping, and prediction indices. The results show that multiscale approaches are essential for integrating local and regional knowledge, offering a comprehensive understanding of the challenges and solutions for the erosive phenomenon. In addition, the geographical distribution of the studies reveals a greater concentration in the states of Goiás and Mato Grosso, associated with the intense agricultural and livestock activity in these areas. It is concluded that interdisciplinary approaches and the use of advanced technologies to address the challenges of linear water erosion should be intensified to promote sustainable land use and management practices.